Meta Analisis Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Matematis Siswa - Nora Susilowaty (LPPM Universitas Advent Indonesia, 2022)
Discovery Learning is a learning model used by researchers to improve students' mathematical abilities. Each discovery learning research on mathematical ability allows different results for the components of mathematical ability, each level of education and the material being taught. Nowadays there is more and more research on discovery learning so it is necessary to review previous research to get accurate conclusions. This study aims to describe the influence of the discovery learning model on the overall mathematical ability of students, based on the components of mathematical ability, based on the level of education and the material being taught. The population in this study is research on the effect of discovery learning models on students' mathematical abilities published from 2018 to 2021. By coding data, 30 studies are obtained that match the criteria. The data analysis technique uses a large effect size analysis. Research result; The implementation of the discovery learning model on students' mathematical abilities as a whole has a major influence with the effect size value of 1, 05, on the mathematical ability component has a major influence on problem solving abilities, the effect size value is 1.18, on the level of education has a major influence on the level of SMP with an effect size value of 1.08, on the material being taught has a major influence on the SPLDV material, the effect size value is 1.94.